Legal AI in High-Stakes Decision Making: Fairness, Transparency, and Accountability Considerations - Munir, Bakht (Journal of Computer Science and Software Applications, 2025)
Artificial intelligence (AI) is transforming legal services, judicial analytics, and regulatory compliance. Recent advances in deep learning and large language models (LLMs) have enabled systems to interpret legal texts, support legal research, and assist in decision making. At the same time, concerns about hallucinations, opacity, and bias have intensified, especially in high-stakes settings involving rights, liabilities, and criminal sanctions. This paper provides a comprehensive review of AI in the legal domain, covering technological foundations, major applications, reliability and hallucination issues, and emerging regulatory responses. We highlight both the opportunities and the risks of deploying AI within courts, law firms, and administrative agencies, and outline design principles for more trustworthy, accountable legal AI systems.